2009
DOI: 10.1016/j.vaccine.2008.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of healthcare workers to accept voluntary stockpiled H5N1 vaccine in advance of pandemic activity

Abstract: Frontline healthcare workers will be at increased risk of infection during the next influenza pandemic. Proactive priming with pre-pandemic vaccine may protect staff and reduce nosocomial transmission. Despite campaigns to increase seasonal influenza vaccine coverage, uptake rates among healthcare workers are generally low, so it is uncertain whether they would participate in voluntary pre-pandemic vaccine programmes. We conducted a cross-sectional questionnaire survey of healthcare workers in a large UK teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 20 publications
4
25
1
Order By: Relevance
“…Deciding in favour of pandemic vaccination increased among those who were vaccinated against seasonal influenza. This result is in line with the findings of other studies (2,16,25,26,33). It seems that when deciding about pandemic immunization, people relied on their experiences with seasonal influenza vaccination and simply behaved as they were accustomed to do in a similar context.…”
Section: Discussionsupporting
confidence: 91%
“…Deciding in favour of pandemic vaccination increased among those who were vaccinated against seasonal influenza. This result is in line with the findings of other studies (2,16,25,26,33). It seems that when deciding about pandemic immunization, people relied on their experiences with seasonal influenza vaccination and simply behaved as they were accustomed to do in a similar context.…”
Section: Discussionsupporting
confidence: 91%
“…In our survey, 70.6% of GPs had received the seasonal influenza vaccine every year in the prior three years and their personal history of seasonal vaccination receipt was strongly related to their acceptability of the A/H1N1 pandemic vaccination with a significant trend towards an exposure-effect relationship. Previous studies conducted among healthcare workers showed a similar relationship between the receipt of influenza vaccine in the previous season and willingness to accept: 1) seasonal influenza vaccine in general practice [27,28], hospitals [29], and long term care facilities [30,31]; 2) pre-pandemic A/H5N1 influenza vaccines in hospitals [22,32]; and 3) A/H1N1 influenza pandemic vaccines in hospitals [22]. In addition, previous receipt of seasonal flu vaccines was associated with willingness to accept unapproved influenza-pandemic vaccination in June 2009 among the general public in the US [14].…”
Section: Resultsmentioning
confidence: 87%
“…[5][6][7] This study contributed to the limited understanding of adverse events following MF59 ® -adjuvanted H5N1 vaccination, particularly outside the clinical settings. Its findings were consistent with prelicensure observations; 2,8 the reported AEFIs were common, nonserious, and anticipated.…”
Section: Discussionmentioning
confidence: 99%